Impact of Company Characteristics on Aggressive Tax Avoidance in Nigerian Listed Insurance Companies - Khadijat Adenola Yahaya; Kabir Yusuf (Universitas Diponegoro, 2020)
Tax avoidance has been identified as one of the tools companies used legally to pay less to government as corporation taxes. This attributed to low revenue target from taxes, thus, holding the continent back by starving the government of the revenue it needs for development. It is against this background, this study examined company characteristics and aggressive tax avoidance in Nigerian listed insurance companies. It assessed the impact of firm size, profitability, leverage and firm age on aggressive tax avoidance of listed insurance companies in Nigeria. The study adopted ex-post facto research design, and data were drawn from the audited annual reports of twenty (20) random sample listed insurance companies between 2010 and 2018. The model of the study was estimated using a two-step system GMM panel model estimator. The results of the study revealed that firm size (coeff of 0.628) and Leverage ( with coeff of 0.549 ) have a positive and significant (p-value < 1% level of significance) impact on aggressive tax avoidance, while firm’ Profitability (coeff of -0.843 ) and Age (with coeff of -0.056 ) have a negative and significant. The study concluded that company characteristics influences aggressive tax avoidance of insurance companies in Nigeria. Specifically, firm’ size and leverage have a positive impact on aggressive tax avoidance in Nigerian listed insurance companies while firm’ profitability and Age have a negative effect on aggressive tax avoidance. Thus, the study recommends among others that firm sixe should be well formulated in accordance with regulating bodies like the Corporate Affairs Commission and National Deposit Insurance Cooperation.